New Territorial Development Tools in the Cohesion Policy 2014-2020 - Györgyi Nyikos (DETUROPE)
Nowadays an important question is how to use the limited resources available in the most efficient and sustainable way. The assessment of development policy interventions and the question of successful absorption of development funds shifted clearly towards stronger enforcement of the aspects efficiency and effectiveness. There is clearly a need for an integrated approach to deliver an effective and sustainable response. The question is how the new territorial development tools – established by the new cohesion policy regulation for the coming programming period - can fit in these conditions, how can they help to achieve the common goals and response to the integrated approach. Cooperation and in-depth knowledge is required for stakeholders to make use of the new tools in an integrated manner.